The Effect of Current Rasio (Cr) and Profit Margin (Npm) on the Share Price of Milk Industry and Trading Company Tbk - Adelin, Dessy (Greenation International Journal of Economics and Accounting, 2024)
This research is the effect of current ratio and net profit margin on the share price of Milk Industry and trading company Tbk. The method used for this research is a descriptive method with a quantitative approach. The type of data used in this research is quantitative data.  The data source used is secondary data, namely data taken from publications made by the Indonesia Stock Exchange. Namely in the form of the Financial Statements of Milk Industry & Trading Company Tbk. in 2013, 2014, 2015, 2016 and 2017. The highest Current Ratio in 2016 was shown at 484.36% and the highest Net Profit Margin in 2008 was shown at 22.29%. Current Ratio and Net Profit Margin do not have a significant effect on stock prices. For investors, Current Ratio and Net Profit Margin do not have a significant influence in making decisions on whether investors will buy, hold or sell shares. In this case, investors want to get dividends from the company's profits and get capital gains from the positive difference between the purchase price and the selling price of the shares. Current Ratio and Net Profit Margin together or simultaneously do not have a significant effect on stock prices.